Prospek Pengembangan Integrasi Usaha Peternakan di Indonesia - Kusuma Diwyanto; A Priyanti; R A Saptati (Caraka Tani: Journal of Sustainable Agriculture, 2006)
Growth of animal husbandry require to be supported by various production equipment, one of them is feed availability. Feed material source of energy come from corn, cassava, paddy bran, grist bran, sago and others, while feed materials source of protein come from soybeans by product, fish meal, leaf leguminous, blood flour and others. Feed materials contain fibrous are grass, paddy hay, sugar cane sprout, husk of cacao and by-product from agriculture food crop represent the feed materials which is exploited for the livestock of ruminants, like cattle, sheep or goat. Opportunity to use agriculture by-product as feed in livestock will represent the challenge and at the same time also to optimize local resources which during the time not yet been exploited efficiently. On the other side, animal husbandry has the constraint in the case of supplying the demand of meat and animal stock. Through the approach  of LEISA (low external input sustainable agriculture), every hectare agriculture field can produce feed material for feeding 2-3 cattle. In this case, livestock personating as compost factory, together with crop by product, which is finally the compost utilized as organic fertilizer for crop. In the effort improving livestock population with the low production cost, pattern of integration between livestock with the plantation and forest, needs to be developed through technical, social and also economic. One of the success key from this pattern in there no materials which unused, and also exploiting innovate correctly and efficient. Through pattern applying integration crop and livestock by external approach of low input, will be provide a livestock product that have a competitive value. For the reason, in the future livestock production through the integration system with crop become enough to draw and have good enough opportunity to be achieved.